2012
DOI: 10.1007/s00383-012-3105-7
|View full text |Cite
|
Sign up to set email alerts
|

Transverse testicular ectopia: three additional cases and a review of the literature

Abstract: Transverse testicular ectopia should be suspected in a boy with an inguinal hernia and contralateral non palpable testis. Trans-septal orchidopexy is recommended when vasa deferentia are fused. Laparoscopy is useful to document the anatomy and to rule out the presence of Müllerian remnants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…[10] To the best of our knowledge, no more than 10 cases in the literature describe the two cases with cross-testicular ectopia and fused vas deferentes in this series. [11] Yıldız et al in their study have reported a six-case series with TTE, which is the largest series showing this rare pathology up to our knowledge. [12] CONCLUSION The six-cases reported in this series had unusual clinical histories for crossed testicular ectopia, such as bilateral undescended testes with palpable or nonpalpable testes, inguinal swelling instead of hernia and unsatisfactory impalpable testes treatment.…”
Section: Discussionmentioning
confidence: 93%
“…[10] To the best of our knowledge, no more than 10 cases in the literature describe the two cases with cross-testicular ectopia and fused vas deferentes in this series. [11] Yıldız et al in their study have reported a six-case series with TTE, which is the largest series showing this rare pathology up to our knowledge. [12] CONCLUSION The six-cases reported in this series had unusual clinical histories for crossed testicular ectopia, such as bilateral undescended testes with palpable or nonpalpable testes, inguinal swelling instead of hernia and unsatisfactory impalpable testes treatment.…”
Section: Discussionmentioning
confidence: 93%
“…Only a few cases are diagnosed preoperatively, while nearly 65% of the cases are diagnosed intraoperatively during hernia repair [5]. There are few reports about CTE diagnosed by clinical examination [3]. The usual presentation of CTE is inguinal hernia with contralateral maldescended testis, but there are some uncommon presentations like CTE with persistent Müllerian duct syndrome, CTE with common vas deferens and bilateral undescended testes [7].…”
Section: Discussionmentioning
confidence: 99%
“…Synonymous terms of this pathology include transverse testicular ectopia, testicular pseudo-duplication, unilateral double testes and transverse aberrant testicular maldescent [3]. Von Lenhossek described the first case in 1886 [4].…”
Section: Introductionmentioning
confidence: 99%
“…In cases of transverse or crossed testicular ectopia, defined as both testicles exciting the same inguinal canal, patients may present with an inguinal hernia and contralateral nonpalpable testis. A high level of clinical suspicion should be used in patients with these findings (Aoki et al 2012;Naji et al 2012). However, the diagnosis is often not made preoperatively (Malik et al 2008).…”
Section: Presentationmentioning
confidence: 99%
“…In the case of transverse testicular ectopia, a transseptal orchiopexy or extraperitoneal transposition of the testis can be used. Laparoscopy should be strongly considered for the diagnosis of remnant Müllerian structures (Malik et al 2008;Naji et al 2012). However, unless their location interferes with orchiopexy, these do not need to be removed as they are not found to be at risk for malignant degeneration and intervention increases risk of injury to the vas deferens or testicular blood supply (Wuerstle et al 2007;Naouar et al 2008).…”
Section: Treatmentmentioning
confidence: 99%